2022
DOI: 10.5424/fs/2022312-19242
|View full text |Cite
|
Sign up to set email alerts
|

VIS/NIR spectra and color parameters according to leaf age of some Eucalyptus species: influence on their classification and discrimination

Abstract: Aim of study: The aim of this study was to verify the differences in VIS/NIR spectra and leaf color parameters of leaves of Eucalyptus badjensis, E. benthamii, E. dunnii, E. grandis, E. globulus and E. saligna, at four ages, and their influence on species discrimination. Area of study: São Mateus do Sul, Paraná, Brazil.           Material and methods: Seedlings of the six species, with four replicates for each, were acclimatized in the same environment, in October 2015, in an entirely randomized de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…On the other hand, the literature describes differences in NIR spectra in function of leaf age, harvesting period, chlorophyll, and nitrogen content, and also physiological characteristics of plants [41][42][43][44]. The similarity in Bertholletia leaves in this study are in accordance with the conclusion of Richardson et al [45]: that evaluating leaves of Picea rubens Sarg.…”
Section: Nir Spectroscopysupporting
confidence: 90%
“…On the other hand, the literature describes differences in NIR spectra in function of leaf age, harvesting period, chlorophyll, and nitrogen content, and also physiological characteristics of plants [41][42][43][44]. The similarity in Bertholletia leaves in this study are in accordance with the conclusion of Richardson et al [45]: that evaluating leaves of Picea rubens Sarg.…”
Section: Nir Spectroscopysupporting
confidence: 90%
“…(2020) reported the wavelengths 5478, 4215, and 7372–7324 cm −1 to be influential in discrimination of rice flour types, while Migacz et al. (2022) reported that the region 2000–2500 nm was essential in differentiation of Eucalyptus species. Reducing the number of wavelengths used in classification model development using large multi‐dimensional datasets like NIRS has the additional advantage of reducing the computational power required for complex algorithms like SVM, thus making it appealing to even resource limited breeding programs.…”
Section: Resultsmentioning
confidence: 99%
“…Although earlier authors working on cassava frog skin disease (Freitas et al, 2020) reported no improvement in the classification accuracy of six classification models using selected influential wavelengths; in this study, the prediction accuracies of PLS-DA and LR algorithms were greatly improved when influential wavelengths were selected (Tables 1 and 2), thus underpinning the importance of identifying and using key wavelengths in developing ML classification models using NIRS spectra. Elsewhere, Sampaio et al (2020) reported the wavelengths 5478, 4215, and 7372-7324 cm −1 to be influential in discrimination of rice flour types, while Migacz et al (2022) reported that the region 2000-2500 nm was essential in differentiation of Eucalyptus species. Reducing the number of wavelengths used in classification model development using large multi-dimensional datasets like NIRS has the additional advantage of reducing the computational power required for complex algorithms like SVM, thus making it appealing to even resource limited breeding programs.…”
Section: Prediction Accuracy Of ML Algorithms Using the Full Spectral...mentioning
confidence: 99%
“…These species are not only native to Australia but have also been grown globally, owing to their wide-ranging applications (Flores et al 2018). They are widely used in construction, pulp and paper production, charcoal manufacturing for steelmaking, honey production, and EO extraction (Migacz et al 2022; Kouki et al 2022). The economic value of Eucalyptus cannot be overstated, given the fact that its essential oils (EOs) are highly sought after in global markets, with a yearly trade volume of one thousand tons (Harkat-Madouria et al 2015).…”
Section: Introductionmentioning
confidence: 99%